Interpretation of the tensile strength of ice under triaxial stress - Nevel, D. E.; Haynes, F. Donald, author.; Cold Regions Research and Engineering Laboratory (U.S.) (Hanover, N.H. : Dept. of Defense, Army, Corps of Engineers, Cold Regions Research and Engineering Laboratory, 1976)
Issued Apr. 1976. Prepared for Office of Research and Development - Office, Chief of Engineers by Corps of Engineers, U.S. Army Cold Regions Research and Engineering Laboratory. Bibliography: p.9. Mode of access: Internet.